Water quality improving device for aquaculture - JIANG ZHIZHONG; MA BENHE; CHEN CUIYUN; DENG WEIMING (2022)
The invention relates to a water quality improving device, in particular to a water quality improving device for aquaculture. The invention provides an automatic improvement water quality improvement device for aquaculture. A water quality improving device for aquaculture comprises a protective shell, a bottom plate, a support, a liquid pumping mechanism and a filtering mechanism. A support is connected to the bottom plate, four protective shells are evenly connected between the bottom plate and the support, a liquid pumping mechanism is arranged between the protective shells and the bottom plate, and a filtering mechanism is arranged in the liquid pumping mechanism. The water pump is started by people, water flows upwards through the screen mesh plate frame and the liquid guide box body under the pumping of the water pump, and when the water makes contact with the activated carbon layer and the sponge layer, the activated carbon layer and the sponge layer adsorb impurities in the water, so that the automatic